تقييم تطبيق استراتيجية تمكين العاملين (دراسة ميدانية على الشركات الصناعيّة العامّة في محافظة اللاذقية) - ميا علي; أحمد نبال (Latakia University Journal - Economic and Legal Sciences Series, 2018)
هدف هذا البحث إلى دراسة مدى تطبيق بُعدي استراتيجية تمكين العاملين(مشاركة العامل في اتخاذ القرار، عدالة وإنصاف الإدارة العليا) في الشركات الصناعية العامة في محافظة اللاذقية، وقد طُبقت الدِّراسة في بالمؤسسة العامة للتبغ وشركة نسيج اللاذقية والشركة العامة للخيوط القطنية باللاذقية، ولتحقيق أهداف الدِّراسة تمَّ توزيع استبانة على العاملين وقد بلغ حجمها(310) وكان منها صالحاً للتحليل(265) استبانة لجمع البيانات ولدراسة مدى تطبيق هذين البعدين، وتمَّ الاعتماد على البرنامج الإحصائيspss، بالإضافة إلى قيام الباحثة بالعديد من المقابلات مع العاملين والمدراء للتعرُّف على واقع العمل أكثر، وكان من أبرز النتائج التي تمَّ التوصل إليها أنَّ الشركات الصناعية العامة تفتقر لأدنى مقومات تطبيق تلك الاستراتيجية وكذلك العامل غير راضٍ عن بيئة العمل التي لا تدعم مشاركته في اتخاذ القرارات الأقرب إلى مجال عمله، وهناك ظلم في الإجراءات والنظم المُطبقة من قبل الإدارة العليا. This study aims to study the extent of applying the two dimensions of the empowerment employees strategy(employees participation in decision-making and the justice and equity of the top management) in the public industrial companies in Latakia. this study was applied in The General Organization of tobacco, textile Latakia Company and the General Company of cotton threads of Latakia, To achieve the purpose of study a questionnaire has been made and distributed to research sample which is(310) workers of these companies, (265) of questionnaires out of total sample is returned and ready for analysis by the statistical program (spss) in order to implementing the study goals. In addition to questionnaire, a several interviews were made with the managers and employees to aware precisely the work environment. the main result of this study was, the public industrial companies lacks to minimum required elements of the implementation of the strategy and workers of these companies isn’t contented and satisfied with the work environment and that is, doesn’t encourage or support workers to take part in decision-making process related to their job, as well as there is injustice in of the work systems followed by top management.